Implementasi E-Katalog dalam Meningkatkan Transparansi dan Akuntabilitas Pengadaan Barang dan Jasa di Dinas Pemuda dan Olahraga (DISPORA) Kota Semarang - Sindu Rizky Utomo; Indra Kertati; Aris Toening Winarni (Jurnal Media Administrasi, 2025)
Government procurement of goods and services is a crucial instrument in achieving transparent, efficient, and accountable governance. One of the key innovations introduced is the e-Catalogue system, an electronic procurement platform provided by the National Public Procurement Agency (LKPP). This study aims to evaluate the implementation of the e-Catalogue in sports equipment procurement at the Youth and Sports Office (Dispora) of Semarang City, focusing on its mechanisms, supporting and inhibiting factors, and its impact on procurement governance. This research employed a descriptive qualitative approach, involving eight informants consisting of structural officials and suppliers. The findings indicate that, in general, the implementation of the e-Catalogue has been effective, particularly in terms of time efficiency, price transparency, and accountability enhancement. However, several challenges remain, including the lack of formal policy dissemination, limited digital literacy among some staff, insufficient internet infrastructure, and unstructured inter-unit coordination. Based on these findings, the study recommends several strategic measures: (1) establishing a permanent inter-unit coordination team, (2) strengthening human resource capacity through continuous training, (3) developing a digital dashboard for real-time monitoring, (4) providing limited public access to procurement reports, and (5) fostering partnerships with suppliers through technical forums and routine evaluations. These measures are expected to optimize the implementation of the e-Catalogue and serve as a best practice model for other local government institutions.